Multiparametric characterization of human T-cell immune synapses by InFlow microscopy - Wabnitz, Guido H.; Samstag, Yvonne (Imaging Flow Cytometry, 2016)
Immune cells need to communicate with each other via direct cell contact formation. The contact zone has similar functions as a neuronal synapse and is therefore named immune synapse. Supramolecular activation clusters consisting of a variety of surface receptors and cytoplasmic proteins are formed within the immune synapse, which are pivotal for T-cell activation. Thus, a malfunction of immune synapse formation has detrimental effects on the healthiness of the individual.Classical confocal microscopy to analyze the supramolecular cluster formation and maturation of the immune synapse between primary human T-cells and antigen-presenting cells is time consuming and the number of cells that can be analyzed is limited. Therefore, we have established an InFlow microscopy approach for the analysis of immune synapses. InFlow microscopy is a hybrid method combining fluorescence microscopy and flow cytometry. Our InFlow microscopy method allows quantifying protein distribution in immune synapses of several hundred or even thousand cell couples in one sample. Importantly, comparisons of different samples with a strong statistical power are possible with InFlow microcopy.